An experimental study on the RV-I expander - Quek, Gary Chin Hwee. (2012)
In effort of saving the ozone layer, the usage of chlorofluorocarbons (CFCs) was stop, alternative refrigerate was needed to replace CFCs, several artificial refrigerate were propose to replace CFCs after years of research, it was found that the all of the artificial refrigerate possess a threat to the ozone layer or the environment as they were unnatural gases. Therefore Carbon Dioxide (CO2) was found to be the most suitable alternative refrigerate.